Research Progress of Ternary Cathode Materials: Failure Mechanism and Heat Treatment for Repair and Regeneration - Tingting Wu; Chengxu Zhang; Jue Hu (Metals)
With the large-scale application of lithium-ion batteries in the field of new energy, many retired lithium batteries not only cause environmental pollution problems but also lead to serious waste of resources. Repairing failed lithium batteries and regenerating new materials has become a crucial path to break through this dilemma. Based on the research on the failure mechanism of ternary cathode materials, this paper systematically combs through the multiple factors leading to their failure, extensively summarizes the influence of heat treatment process parameters on the performance of recycled materials, and explores the synergistic effect between heat treatment technology and other processes. Studies have shown that the failure of ternary cathode materials is mainly attributed to factors such as cation mixing disorder, the generation of microcracks, phase structure transformation, and the accumulation of by-products. Among them, cation mixing disorder damages the crystal structure of the material, microcracks accelerate the pulverization of the active substance, phase structure transformation leads to lattice distortion, and the generation of by-products will hinder ion transport. The revelation of these failure mechanisms lays a theoretical foundation for the efficient recycling of waste materials. In terms of recycling technology, this paper focuses on the application of heat treatment technology. On the one hand, through synergy with element doping and surface coating technologies, heat treatment can effectively improve the crystal structure and surface properties of the material. On the other hand, when combined with processes such as the molten salt method, coprecipitation method, and hydrothermal method, heat treatment can further optimize the microstructure and electrochemical properties of the material. Specifically, heat treatment plays multiple key roles in the recycling process of ternary cathode materials: repairing crystal structure defects, enhancing the electrochemical performance of the material, removing impurities, and promoting the uniform distribution of elements. It is a core link to achieving the efficient reuse of waste ternary cathode materials.